Photoluminescence, Scanning Electron Microscope and Atomic Force Microscope Analyses of Organic NLO Single Crystal of Hippuric Acid for Opto-electronic and Photonic Applications - Mahalakshmi, N.; Parthasarathy, M. (Journal of Scientific Research, 2024)
A bulk single crystal of Hippuric acid (HA) was grown by a low temperature solution growth technique. The unit cell parameters were confirmed by single crystal X-ray diffraction. The optical transmittance of grown crystal was determined by UV-Vis-NIR analysis and the lower cut-off wavelength was observed at 304 nm. The Urbach energy shows HA has good crystallinity. Photoluminescence study reveals the suitability of the grown crystal for near- violet fluorescence emission. The electronic polarizability was calculated by using Lorentz-Lorenz equation. Scanning Electron Microscope (SEM) analysis, reveals that the material surface is like layer structure. Atomic Force Microscope (AFM) analysis was used to analyse the surface roughness of the grown material.